Exploring Anti-Fungal, Anti-Microbial and Anti-Inflammatory Properties of a Topical Non-Steroidal Barrier Cream in Face and Chest Seborrheic Dermatitis - Balato, Anna (Dermatol Ther (Heidelb), 2019)
INTRODUCTION: The pathogenesis of seborrheic dermatitis (SD) is multifactorial and traditional treatments may not target all aspects of it. The aim of this study was to evaluate short-term anti-fungal, anti-microbial, anti-inflammatory and anti-pruritus properties of a novel non-steroidal cream (NSC) containing piroctone olamine, zinc salt of l-pyrrolidone carboxylate (PCA), hydroxyphenyl propamidobenzoic acid, biosaccharide gum-2 and stearyl glycyrrhetinate in patients with face and chest SD. METHODS: Twelve male subjects affected by SD, presenting face and chest manifestations, were enrolled. Patients were instructed to apply NSC twice a day, performing regular visits at baseline (W0), after 7 (W1) and 14 (W2) days of treatment. A limitation of the study was that no control group treated with the vehicle without active ingredients was enrolled. To evaluate the efficacy of the NSC, investigator’s assessments were represented by scoring index (SI) and investigator’s global assessment score (IGA). In order to assess NSC anti-fungal and anti-microbial effects, skin scale scrapings were collected and used for Malassezia furfur (MF) and Staphylococcus epidermidis (SE) cultures. In parallel, in order to assess NSC anti-inflammatory effects, gene expression of IL-1α, IL-1β, IL-6, IL-8, and TNF-α was assessed. In addition, anti-pruritus effects were also evaluated through gene expression of cathepsin S and l-histidine decarboxylase. RESULTS: SI mean scores significantly decreased at W1 and, to a greater extent, at W2 compared with W0. The IGA score registered an important improvement efficacy both for face and chest, from W1 to W2. MF and SE growth was already inhibited at W1, with a more pronounced decrease at W2. Gene expression of all analyzed mediators was significantly reduced at W1 compared to W0. CONCLUSION: In conclusion, our assessment is that NSC is an effective and well tolerated treatment option for SD with anti-fungal, anti-microbial and anti-inflammatory properties. TRIAL REGISTRATION: ISRCTN registry, ISRCTN77871064 (retrospectively registered October 17, 2019). EudraCT number, 2019-003813-32. FUNDING: ISDIN.